1994
DOI: 10.1046/j.1471-4159.1994.62041596.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase FA/Glycogen Synthase Kinase‐3 Predominantly Phosphorylates the In Vivo Site Thr97‐Pro in Brain Myelin Basic Protein: Evidence for Thr‐Pro and Ser‐Arg‐X‐X‐Ser as Consensus Sequence Motifs

Abstract: In a previous study, protein kinase FJglycogen synthase kinase-3 (F,/GSK-3) was identified as a myelin basic protein (MBP) kinase associated with intact brain myelin. In this report, the phosphorylation sites of MBP by kinase F,/GSK-3 were further determined by two-dimensional electrophoresis/TLC, phosphoamino acid analysis, tryptic peptide mapping, Edman degradation, and direct sequencing. Kinase F,/GSK-3 phosphorylates MBP on both threonine and serine residues. Three tryptic phosphopeptide peaks were resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…35 As shown in Figure 1D, GSK3β derived from P493-6 cells grown in decreasing amounts of Tet displayed significantly increased kinase activity. This activity was inhibited by treatment with the specific GSK3β inhibitor BIO.…”
Section: C-myc Induction Results In Activation Ofmentioning
confidence: 79%
“…35 As shown in Figure 1D, GSK3β derived from P493-6 cells grown in decreasing amounts of Tet displayed significantly increased kinase activity. This activity was inhibited by treatment with the specific GSK3β inhibitor BIO.…”
Section: C-myc Induction Results In Activation Ofmentioning
confidence: 79%
“…The PMA-stimulation also induced phosphorylation of MBP at Thr98, the site phosphorylated by both MAPK and GSK-3β [56,57]. (This threonyl residue in the human 18.5-kDa MBP sequence corresponds to residues Thr95/Thr97 in the murine/bovine 18.5-kDa MBP sequences, respectively [11,15,35,74]).…”
Section: Discussionmentioning
confidence: 99%
“…Using a phospho-specific antibody toward Thr98 (human 18.5-kDa sequence; bovine Thr97; murine Thr95) of MBP, an identified MAPK [56] and GSK-3β [57] phosphorylation site, we found that there was an overall increase in Thr98-phosphorylated MBP-C1 in PMA-stimulated N19-OLGs, including at ruffling sites (Fig. 2b).…”
Section: Classic 185-and 215-kda Mbp Isoforms Localize To Membrane-mentioning
confidence: 99%
“…MBP can be phosphorylated in vitro by protein kinase C, protein kinase A, glycogen synthase kinase (GSK), calmodulin-dependent kinase, and mitogen-activated protein kinase (MAPK), enzymes all present in myelin [4,[78][79][80][81][82]. The in vitro sites of phosphorylation differ in some cases from those found to be phosphorylated in myelin MBP in vivo [56,67], but one of the in vivo sites, Thr97 (bovine sequence), is phosphorylated by MAPK and GSK in vitro [78,79]. However, the sites of phosphorylation of MBP in OLs, as opposed to mature myelin, are not known and may include some of the in vitro phosphorylation sites.…”
Section: Post-translational Modifications Of Mbpmentioning
confidence: 99%